The Influence of Carbon Powder on the Physical, Mechanical and Absorption Properties of Carbon Foam from Natural Precursor Starch - Mohamed Nasrul Mohamed Hatta; Muhammad Shamim Amir Mohd Nasir; Kamarul Azhar Kamarudin (International Journal of Integrated Engineering, 2025)
This study was fabricated the starch-based carbon foam with sodium borate as the blowing agent and reinforced with carbon powder. The effect of carbon powder on the physical, mechanical and adsorption properties was investigated. The temperature of foaming and carbonization was fixed but the carbon powder percentage was varied in the range between 2wt% to 8wt%. The physical properties of the carbon foam analysed by the density and porosity, pore morphology was analysed by using Scanning Electron Microscopy (SEM) and carbon bonding was observed through Fourier-infrared Spectroscopy (FTIR). The percentage of the carbon powder inside the carbon foam influence the properties of the carbon foam. The higher the content of the carbon powder, the higher the bulk density but low porosity. The results of the pore morphology using the SEM proved the size of the pore decreases as the carbon powder percentage increase inside the carbon foam. The FTIR analysis shows the carbon bonding. Furthermore, the maximum stress and maximum force applied also rises as the carbon powder increases. The highest value of maximum stress was achieved by carbon foam with 8wt% of carbon powder which is 1.71345 N/mm² respectively. Since the bulk density is higher, the oil adsorption lower due to small porosity of the carbon foam. The characteristic remains for all parameters when the reusability test implemented by burning the carbon foam. The objectives of the study achieved and the effect of carbon powder to carbon foam proven.